دور حروف المعاني في تحديد الأحكام الفقهية؛ دراسة فيكتاب المجموع للإمام النووي - Dollah, Nafi@Hanafi; hussin, Mohd Noor (FAKULTI PENGAJIAN PERADABAN ISLAM, KUIS, 2016)
ABSTRACT The Arabic syntax is closely related to Ilm Fiqh as they are inseparable from one another. With that, we can see Muslim scholars discussing Arabic grammar in their kitab. Grammarians have also tried to relate Arabic grammar with Nusus Fiqhiyah from Quranic ayat and Hadiths. Imam Nawawi was among the scholars who focused and discussed Arabic grammar in his Majmu'. The discussion of Arabic syntax in this book is numerous. Therefore, the researcher is interested to study his discussion on syntactic issues by focusing on Huruf al-Maani. This study is based on descriptive and analytical methodologies. The study found that Ilm Nahw indeed helps in understanding Shariah texts. The study also found that Imam Nawawi was an expert in the field of Ilm Nahw which is manifested through his discussion and debate on the issues of Huruf al-Maani on Fiqh.